Entrepreneurship Education and Entrepreneurial Intention among Disability Students in Higher Education - Maulida, Ernita; Nurbaity, Esty; Utami G. P, Vera (KnE Social Sciences, 2020)
Entrepreneurship education helps to form appropriately entrepreneurial mindsets and behaviors in students. This is not only for normal students but also students with special needs in tertiary institutions. This study aims to identify the entrepreneurial intention of students with special needs (disability) at Jakarta State University (UNJ). This research used the case study research method, where the casesare students with disabilities at UNJ who are registered as active students. Data was collected using unstructured interviews. The research revealed three core indicators of student entrepreneurial intention. These are 1) elements of intention (cognition, emotions and conations), 2) characteristics of an entrepreneur and 3) business ethics. The results of this study state that students with disabilities know about entrepreneurship (cognition) and have a desire to become an entrepreneur (emotion) and have experience in trying entrepreneurship (conations). In addition, the students with disabilities also know what needs to be prepared to become an entrepreneur such as the readiness of the risks to be faced and how to run a good business. Keywords: entrepreneurship education, disability student, higher education, entrepreneurial intention